The Internet and Prospective Engineers: Results Analysis for Studies Conducted During the Pandemic - Soloveva, Rimma A. (2020)
The relevance of the study is justified by transition to distance learning that modifies the learning methods and principles during the pandemic to conform to remote training needs of students majoring in Land Management and Cadastres at Arctic State Agrotechnological University (ASAU). of the Republic of Sakha (Yakutia). The study objective was to substantiate the interaction between ASAU students and teachers in remote training organization within the pandemic period using network technologies. The study monitored the educational process dynamics during the pandemic. The study results evidence that during the pandemic, a particular priority in educational process arrangement at ASAU was given to enhancing the professional readiness of students and teachers and building up their competence in organizing their professional activities using the Internet in compliance with the latest requirements of the Federal State Educational Standards. The reference and experimental groups were sampled based on students’ interviews during the transition to remote access Internet-based educational process.  The practical implications of the study lie in identifying the distinctive features of teachers’ and students’ educational activities at ASAU during the pandemic. These results can be adapted and implemented in the system of prospective engineers’ training in other regional universities in the north-east of Russia.